INTEGRATED PEST MANAGEMENT - G.S. Dhaliwal; Ramesh Arora (Ludhiana Kalyani)
This book considered to be substainable, environment frendly, biodiversity conservative, economically feasible and socially acceptable.
Dynamics Of Pest Population Integrated Pest Management Botanical Pest Control
Keywords: Dynamics Of Pest Population ,Integrated Pest Management ,Botanical Pest Control